ANALYSIS OF FACTORS RELATING TO PREGNANT WOMEN'S IRRANGEMENT IN CARRYING OUT PREGNANCY EXAMINATION AT THE KRUENG BARONA JAYA PUBLIC HEALTH CENTER, ACEH BESAR - Ade Mursalina; Maidar; Nurjannah (International Journal of Medical Science and Public Health Research, 2024)
Pregnancy is a physiological process that requires special attention in efforts to maintain the health of both mother and baby. One of the efforts that can be done is regular antenatal care (ANC) check-ups. However, there are still many pregnant women who have not undergone ANC with the desired regularity. Therefore, this study was conducted to identify factors related to the irregularity of prenatal check-ups. This study is a quantitative analytic study with a cross-sectional approach. The population in this study consisted of 294 pregnant women who had given birth in the Krueng Barona Jaya region, Aceh Besar. The sampling method used total sampling, where out of 294 pregnant women, 7 of them did not have or bring their KIA book, 39 could not be found or contacted, and 3 individuals were unwilling to become respondents. Hence, a total sample of 245 respondents was used in this study. The results of the analysis showed that factors related to the irregularity of ANC check-ups were poor knowledge (OR=15.61; 95% CI=2.50-97.39; P=0.003), lack of media exposure (OR=4.87; 95% CI=1.51-15.70; P=0.008), and previous experience (OR=2.99; 95% CI=1.02-8.76; P=0.046). The conclusion of this study is that knowledge, media exposure, and prior experiences influence the irregularity of prenatal check-ups. Here, prior experiences refer to the healthcare experiences received during previous check-ups or pregnancies. Attitude, as well as pregnancy intentions and planning, do not significantly correlate with irregular ANC check-ups. Therefore, efforts are needed to enhance knowledge and provide better media resources regarding the importance of prenatal examinations, as well as to improve the overall healthcare experience for pregnant women.